Access to knowledge : new information technologies and the emergence of the virtual university - Tschang, F. Ted ;Senta, Tarcisio Della (Amsterdam : Elsevier Science, 2001)
This volume arose out of the United Nations University/Institute of Advanced Studies' Virtual University Initiative. One of the aims of this initiative was to study and analyze collected thoughts on the potential of virtual education to solve educational problems around the world. Another objective of the VU Initiative is the development of software systems for virtual education. These two activities were synergistic, in that we could confirm our ideas for the book through these other substantial research and implementation activities; and in how the book project itself informed the VU Initiative's other activities. This book was initially planned as an input to the UNESCO World Conference on Higher Education, held in Paris in October 1998. But it became much larger than that. In such a conference, much of the time is often taken up by political and institutional issues, and general principals and speeches. Our effort then became one of intellectually contributing a coherent and structured "map" to the trends and issues in virtual education.
Part I. Knowledge-based perspectives on learning -- Part II. Transforming learning environments with new technologies -- Part III. Moving toward the virtual university: institutional experiences from different regions.
Includes bibliographical references and index.
Keywords: DISTANCE EDUCATION